On the way to 2020: data for vocational education and training policies : country statistical overviews - (:unkn) unknown (Publications Office of the European Union, 2014)
"European policy-making in vocational education and training (VET) needs to be supported by sound quantitative information. Cedefop has selected a set of 32 statistical indicators to quantify key aspects of VET and lifelong learning, based on their policy relevance and importance for achieving the Europe 2020 objectives. The aim is to help describe, monitor and compare countries. This update incorporates new hard evidence from the European statistical system. The indicators do not claim to assess national systems or policies but should be used as headline figures for reflecting on progress towards the strategic objectives set for Europe. The indicators take 2010 as the baseline year and present statistical overviews for the 28 European Union Member States and the former Yugoslav Republic of Macedonia, Iceland, Norway, Switzerland and Turkey." (Hrsg., BIBB-Doku)
Keywords: S System beruflicher Bildung; T 3.5 Statistik; I 2.2 Europa; Berufsbildungssystem; Monitoring; Indikatoren; Europa; Türkei